Forming buyer coalitions with bundles of items - Boongasame, Laor; Leung, Ho Fung; Boonjing, Veera; Chiu, Dickson K.W. (My University, 2009)
There are several existing buyer coalition schemes, but they do not consider bundles of items. This research presents an algorithm for forming a buyer coalition with bundles of items, called the GroupBuyPackage scheme, in order to maximize the total discount. Our simulation results show that the total discount of the coalitions in this scheme are close to that in the optimal scheme. © 2009 Springer Berlin Heidelberg.
Keywords: Bundles of items; Coalition formation; Cooperative game theory; Group buying